Optimizing Marine Governance in the Kepulauan Riau for Ecosystem Sustainability and Economic Welfare - Putri, Hena Salsabila; Anita, Fahriana Nur; Aulija, Nelinia; Amalia, Dinda (Journal Governance Bureaucratic Review, 2024)
Kepulauan Riau, an Indonesian province rich in marine resources, faces significant challenges in managing its coastal ecosystems and sustainable economic development. Despite the region's vast marine potential, including fisheries, tourism, and natural gas reserves, issues such as illegal, unreported, and unregulated (IUU) fishing, marine pollution, and ecosystem degradation threaten its sustainability. This study aims to explore the optimization of marine governance in Kepulauan Riau, focusing on balancing ecosystem protection with economic welfare for coastal communities. A qualitative approach was employed, utilizing a literature review of scientific articles, government reports, NGO publications, and books related to marine governance and sustainable resource management. The findings highlight the need for stronger law enforcement, enhanced community participation, and the development of marine ecotourism and aquaculture as sustainable alternatives. The study also emphasizes the importance of integrating digital technologies for better fisheries management and monitoring. In conclusion, optimizing marine governance in Kepulauan Riau requires a holistic approach that incorporates community involvement, technological innovation, and policy reforms to ensure long-term sustainability and improve economic welfare for local populations. Effective governance will not only safeguard marine ecosystems but also drive inclusive economic growth in the region.